Studi Kasus: Edukasi Aspek Preventif pada Pengelolaan Hipertensi - Syahrizal, Syahrizal; Kurniawan, Hendra; Wijaya, Nanda; Rifqatunnisak, Rifqatunnisak; Anggreiny, Cut Dini (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
Hypertension is defined as an increase in systolic blood pressure exceeding 140 mmHg and/or diastolic blood pressure exceeding 90 mmHg. Hypertension is a highly prevalent disease that requires a preventive approach to avoid complications and improve patients' quality of life. This study aims to establish preventive measures for hypertensive patients through family education and home visits. The study adopts a descriptive qualitative approach using case study methods, including interviews, observations, documentation, and family assessments. Interventions involve education on diet, healthy lifestyle practices, exercise, and medication adherence. After one week of intervention, the patient's blood pressure significantly decreased from 160/97 mmHg to 137/88 mmHg. The patient demonstrated improved compliance, including reduced consumption of high-salt foods, increased light physical activity, and adherence to prescribed medications. This study highlights the importance of a low-salt and low-fat diet, regular exercise, and family support in managing hypertension and improving patients' quality of life. In conclusion, intensive education-based interventions and effective family involvement can reduce the severity of hypertension and prevent further complications.